'You just appreciate every little kindness': Chinese language teachers' wellbeing in the UK. (February 2021) - Jin, Jun; Mercer, Sarah; Babic, Sonja; Mairitsch, Astrid
Abstract: Drawing on a positive psychology perspective, a resource-based view of wellbeing, and an ecological perspective, this article provides an in-depth account of Chinese language teachers' wellbeing in the UK. Semi-structured interviews were conducted with 7 teachers who teach Mandarin Chinese as a foreign language (CFL) at secondary-school level in the UK. This study identified four ecological systems that interconnected with one another that are associated with these CFL teachers' wellbeing: the ecology of the school, the ecology of work and life, the ecology of the education system, as well as the societal ecology of teaching generally and modern foreign languages (MFL) specifically. The study also found that these CFL teachers drew on a number of psychological, social, and contextual resources to manage their wellbeing and remain positive in the face of challenges. This study provides an ecological understanding of CFL teacher wellbeing in the UK and offers a broader lens for the design and implementation of effective prevention, intervention, and remedial actions to address teacher wellbeing.